Legal Standards in The Sacred Scripture “Avesta” “Videvdat” - Karimova A.I. (Euro Asian Journal Publishing, 2024)
The article discusses the legal norms in the holy scripture “Avesta” and their main role. Aspects of the Videvdat code in the education of Zoroastrians are studied based on the main criteria of good and evil. The types of crimes and what punishments are accepted according to criminal law are considered. The article also focuses on the features of showing deep respect for nature according to the Avesta and regulating property relations of those times
Keywords: Avesta; Zoroastrianism; establishment